Disaster management and faith-based organizations, an Islamic perspective - Bouafia, Mohammed; Zahari, Rustam Khairi (2013)
Regarding its complexity which overwhelms the capacity of the affecting community to cope with, disaster is increasingly recognizing the necessity to ultimate response drawing on an extensive variety of skills and manpower. It requires collaboration between various serving services including government, private sector, local communities and faith-based organizations due to limited available recourses. The purpose of this paper is to address the richness of Islamic teaching in disaster management in order to improve the Islamic based organizations‟ participation in reducing the impacts during disaster situations. Data were collected through journals, articles, reports and documents analysis. Therefore, several investigations have been reviewed. The paper introduces an overview of disaster management, act of god, view of Islam on disaster management, and faith-based organizations contribution in disaster management. It has been found that Islamic basedorganizations usually have advantage and great potential to offer immediate assistance in disaster events and to involve in long-time recovery operations when outside agencies return back home.